Rapidly progressing and resistant warts in an immuno-competent male (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Cutaneous warts are common skin conditions caused by different specific strains of the human papilloma virus (HPV), mostly affect children as localized lesion on the hands and feet. They are slowly progressing and disseminated lesions are found in immuno-compromised situations. Usually majority of warts disappear by few months to two years. This is a case of extensive, giant, rapidly progressing and resistant warts in an immuno-competent adult male.